Hyper‐reactive cloned mice generated by direct nuclear transfer of antigen‐specific CD4+ T cells. (3rd May 2017) - Kaminuma, Osamu; Katayama, Kazufumi; Inoue, Kimiko; Saeki, Mayumi; Nishimura, Tomoe; Kitamura, Noriko; Shimo, Yusuke; Tofukuji, Soichi; Ishida, Satoru; Ogonuki, Narumi; Kamimura, Satoshi; Oikawa, Mami; et al.
Abstract: T‐cell receptor (TCR)‐transgenic mice have been employed for evaluating antigen‐response mechanisms, but their non‐endogenous TCR might induce immune response differently than the physiologically expressed TCR. Nuclear transfer cloning produces animals that retain the donor genotype in all tissues including germline and immune systems. Taking advantage of this feature, we generated cloned mice that carry endogenously rearranged TCR genes from antigen‐specific CD4 + T cells. We show that T cells of the cloned mice display distinct developmental pattern and antigen reactivity because of their endogenously pre‐rearranged TCRα (rTα) and TCRβ (rTβ) alleles. These alleles were transmitted to the offspring, allowing us to establish a set of mouse lines that show chronic‐type allergic phenotypes, that is, bronchial and nasal inflammation, upon local administrations of the corresponding antigens. Intriguingly, the existence of either rTα or rTβ is sufficient to induce in vivo hypersensitivity. These cloned mice expressing intrinsic promoter‐regulated antigen‐specific TCR are a unique animal model with allergic predisposition for investigating CD4 + T‐cell‐mediated pathogenesis and cellular commitment in immune diseases. Synopsis: TCR‐transgenic mice are important tools to analyze antigen‐response mechanisms. This study describes the generation of antigen‐specific mice cloned from T cells, which exhibit rearranged TCR‐dependent antigen reactivity and allergic predispositions. Cloned mice were successfully generated from antigen‐specific CD4 + T cells. Rearranged TCRα/β were required for their heritable in vitro antigen reactivity. Mice with either rearranged TCRα or TCRβ develop allergic bronchial and nasal inflammation. Abstract : TCR‐transgenic mice are important tools to analyze antigen‐response mechanisms. This study describes the generation of antigen‐specific mice cloned from T cells, which exhibit rearranged TCR‐dependent antigen reactivity and allergic predispositions.